Discreteness and the welfare cost of labour supply tax distortions - Keshab Bhattarai; John Whalley (The University of Western Ontario, Department of Economics, 2002)
We compare the welfare costs of tax distortions of labour supply in one and two member household discrete and continuous labour supply (leisure consumption) choice models. In the discrete models taxes induce a large response from a subset of the population, while the majority of the population exhibits unchanged behaviour. In contrast the majority of the population reacts to tax changes in continuous models. Models are made comparable by calibrating to the same aggregate uncompensated labour supply elasticities in discrete and continuous models. The welfare costs of similar taxes are significantly different when individuals face discrete labour supply choices than when they choose working hours continuously, and vary with tax rates in different ways. Analysis of results from these models show that discrete choice matters in the assessment of the costs of labour supply tax distortions.
Keywords: D58; D60; H23; H31; 330; discreteness; labour supply; welfare; taxes; equilibrium